Analysis of Tensile Strength of Carbon Fiber and E-Glass Sandwich Composite Materials with Balsa Wood Core Based on Polyester - Banowati, Lies; Bekti Suroso; Robert Parulian (Jurnal Ilmiah Teknik, 2025)
Sandwich composite is a type of structural composite material composed of two outer layers (skins) and a core material in the middle. There are various definitions of sandwich composites, but a key factor is the lightweight core, which reduces the material’s specific weight, coupled with the rigidity of the skin layers that provide strength to the sandwich composite. This research aims to determine the tensile strength of carbon fiber and glass fiber sandwich composite materials with fiber orientations at 0°, ±45°, and (0,90)°, using a 3 mm thick core. The matrix used is polyester Yukalac 2250 BW-EX. Tensile testing is conducted following ASTM D3039 standards. Based on the tensile test results, the highest tensile strength is observed in the carbon-balsa/polyester sandwich composite with a 0° fiber orientation, achieving an average tensile strength of 152.71 MPa. On the other hand, the lowest tensile strength is found in the e-glass-balsa/polyester sandwich composite with a ±45° fiber orientation, with an average tensile strength of 12.34 MPa.